THE IMPLEMENTATION OF PEER FEEDBACK IN EFL WRITING CLASS - Muflihah, Tatik; Authar, Nailul (Universitas Islam Balitar, 2021)
This study investigates the implementation of peer feedback in writing class. The participants were EFL students in a private university in Surabaya who took essay writing subject in academic year 2020-2021. This study found that the implementation of peer feedback was perceived as a positive activity for writing performance. Students preferred peer feedback because of several reasons, such as: to detect writing problems, to write better in terms of grammar, to analyze writing and paragraph development and spelling. Most students wrote that peer feedback refers to providing comments and suggestions rather than judging each other work. They found that from several aspects of writing, grammar is the most important aspect that must be corrected among other. They confirmed that grammar is vital because it decides on how formal the writing should be and it is a crucial aspect for ensuring the writer’s point is getting across. Another aspect is paragraph development. It is another fundamental aspect of writing since it links the writer’s ideas to the readers. Furthermore, students affirmed that peer feedback can be used as a means to re-conceptualize students’ thinking. This is a meaningful contribution for students critical thinking and to improve autonomy. Therefore, peer feedback facilitates students wider opportunity to develop writing which further lead to self-determination learner.